2020
DOI: 10.1016/j.compositesa.2020.105922
|View full text |Cite
|
Sign up to set email alerts
|

Measurement of manufacture assembly stresses in thick composite components using a modified DHD method

Abstract: Understanding of the through-thickness distribution of assembly stresses caused by manufacture process-induced distortion (PID) in thick composite components is essential for safety and reliability assessment. Inspired by deep-hole drilling (DHD) method which is widely used to reconstruct residual stresses in thick metallic components, current research attempts to extend and modify the DHD technique to measure the manufacture assembly stresses in composite components. It is observed that the modified DHD techn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
2
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(3 citation statements)
references
References 25 publications
0
2
0
Order By: Relevance
“…However, it was still possible to measure assembly stresses but some significant calculation errors were found. A study from Hu et al [ 29 ] went on to modify the approach taken by Garza et al by implementing an integrating stress calculation method, finding this reduced calculation errors and gave results for assembly stress which matched well with simulations.…”
Section: Destructive Methodsmentioning
confidence: 94%
See 1 more Smart Citation
“…However, it was still possible to measure assembly stresses but some significant calculation errors were found. A study from Hu et al [ 29 ] went on to modify the approach taken by Garza et al by implementing an integrating stress calculation method, finding this reduced calculation errors and gave results for assembly stress which matched well with simulations.…”
Section: Destructive Methodsmentioning
confidence: 94%
“…There has been a huge breadth of research that has been undertaken in the numerical modeling of the manufacturing process of fiber reinforced laminates, as Baran et al [3] showed. It is clear that much progress has been made over the past few decades and it is now possible to accurately predict many physical phenomena accurately by choosing and correctly implementing one of the [11,[13][14][15][16] Hole-drilling [19,27] [20] -Potentially global scale if laminate is thin -Bixal stress distribution -Accuracy decreases with depth of cut [17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32][33][34] Ring-core [40][41][42] Note: ?, there is potential but it has not been done to date; , it is possible with some caveats. many models and techniques available.…”
Section: Discussionmentioning
confidence: 99%
“…The strain changes are measured and processed [98,114]. This method is also used with a combination of speckle interferometry [115][116][117][118], Moire´s interferometry, and holographic interferometry [119][120][121][122].…”
Section: Other Stress Relaxation-based Techniquesmentioning
confidence: 99%